The Effects of Reading Habit and Vocabulary Mastery towards Students’ Listening Skill at State Senior High Schools in East Jakarta - Frijuniarsi, Nurul; Marlianingsih, Noni (Bina Nusantara University, 2016)
This research was aimed to get empirical data and analyze the effects of reading habit and vocabulary mastery towards student’s speaking skill at private vocational schools in East Jakarta. This research used data analysis technique, those were descriptive statistic, requirement analysis, normality test, linearity test, and test of hypothesis (analysis of inferential). The research was held at State Senior High Schools in East Jakarta. Data collection was done by giving a test for reading habit, vocabulary mastery and listening skill to tenth-grade students at SMA 105 Ciracas and SMA 98 Cijantung. Due to the result, it can be inferred that there is an effect of reading habit towards student’s speaking skill.